IMPACT OF VARIATION OF GREASE VOLUME ON BALL BEARINGÃâÃâS CHARACTERISTICS - ADHITYA PRATAMA (NIM : 13106154); Tim Pembimbing : Dr. Ing. Tri Yuswidjajanto Z; Prof. Wirant, BOBBY
The machines are expected to operates at its optimum condition. This condition influenced by the efficiency each of every component. One of the machine majority component is the shaft. Shaft is one of the rotating equipment that its efficiency influenced by the friction on its bearing. Ball bearing is the most commonly and wide range application bearing type that used for shaftÃ‚Â’s bearing. The friction that occurs on the bearing is classificated as dynamic friction because it influenced by other factor such load, rotational speed, lubricant type, and lubricant filling volume. This research conducted in order to gain correlation between ball bearing coefficient of friction with grease filling volume in term of load and rotational speed. The research shows that as the grease volume increasing from 1/3 to 3/3, for 470 rpm, the increases of coefficient of friction become 69.2% and 88.5%. And then as the increasing load until reaches the maximum load the increases of coefficient of friction become 20.9% and 34.9%. Overall, the coefficient of friction, temperature, and consumed electricity power are increasing as the increasing grease volume but the noise is reducing.